Classroom Interaction in an Online Speaking Class - Rahma Vindyasari; Francisca Maria Ivone; Primardiana Hermilia Wijayati (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The qualitative study aims to look into the patterns and characteristics of interaction in an online speaking course. This research was conducted at Sekolah Vokasi Universitas Gadjah Mada (UGM) Yogyakarta's Oral English for Daily Communication Class of the Applied English Study Program. The researcher observed the online learning sessions to learn about the online teaching and learning process synchronously on Google Meet. The findings revealed that the teacher and students produced various patterns of interaction involving teacher-class, teacher-student, student-teacher, student-student, and teacher-group interaction, as well as mixed interaction features such as confirmation check, code switching, self-repetition, clarification request, elicitation, completion, other-repetition, and correction.Abstrak: Tujuan dari penelitian kualitatif ini adalah untuk melihat pola dan karakteristik interaksi yang terjadi dalam kelas berbicara yang dilaksanakan secara daring. Penelitian ini dilaksanakan di Kelas Komunikasi Harian Sekolah Vokasi Universitas Gadjah Mada (UGM) Yogyakarta Program Studi Bahasa Inggris Terapan. Peneliti mengamati sesi pembelajaran daring untuk mempelajari proses belajar mengajar yang berlangsung sinkron di Google Meet. Hasil analisa data menunjukkan bahwa guru dan siswa menghasilkan berbagai pola interaksi yang melibatkan interaksi guru-kelas, guru-siswa, siswa-guru, siswa-siswa, dan interaksi guru-sekelompok siswa, serta berbagai macam fitur interaksi seperti confirmation check, code switching, self-repetition, clarification request, elicitation, completion, other-repetition dan correction.